Mesures de prévention et de protection des risques liés à la présence du gaz sulfure d’hydrogène au sein des sites de traitement des hydrocarbures - محمد زهير, بوزنادة; زياد عبد المنعم, بوزنادة; محمد فيصل, بوزنادة (University of El-Oued, 2022)
"During our field visit to SH-FCP, we touched on all the facilities, such as the exploitation regulations, the regulations, and the methods of protection in force, and we noted a lack of preventive measures for hydrogen sulphide gas. Our work focuses on introducing the poisonous hydrogen sulphide gas, where we explained its physical and chemical properties and its danger to the health of workers, equipment and the environment. with him and an ambulance in case of exposure to him. We also studied a real case of worker exposure to this gas, which led to his death. We detailed how he suffocated and the causes of this accident." خلال زيارتنا الميدانية الى مجمع ( FCP-SH )تطرقنا الى جميع المنشآت كأنظمة الاستغلال و أنظمة و طرق الحماية المعمول بها و لاحظنا نقص في التدابير الوقائية الخاصة بغاز كبريتيد الهدروجين يركز عملنا هذا على التعريف بغاز كبريتيد الهيدروجين السام حيث وضحنا خصائصه الفيزيائية و الكيميائية و خطورته على صحة العمال و المعدات و المحيط كما تطرقنا الى مصادره الطبيعية و الصناعية ,قدمنا كذلك طرق الوقاية و الحماية منه كتجهيزات الموقع بالأجهزة الوقاية و توصيات منضمات الصحة مع كيفية التعامل معه و الاسعاف في حالة التعرض له ايضا قمنا بدراسة حالة حقيقية لتعرض عامل لهذا الغاز مما ادى الى وفاته حيث قمنا بتفصيل في كيفية اختناقه واسباب هذه الحادثة
مذكرات ماستر تخصص بيتروكيميائية
Keywords: hydrogen sulphide, prevention and protection measure, security system; كبريتيد الهيدروجين، إجراءات الوقاية والحماية، نظام الأمان